Performance Assurance for IT Systems - King, Brian (CRC Press, 2009)
Performance Assurance for IT Systems emphasizes the importance of addressing performance and technology-related issues from the beginning of the planning process, at the feasibility and bid stages. It promotes the concept of Performance Assurance throughout the entire system lifecycle, covering technology, relevant processes, and people-related topics.